Metaphylactic effect of minerals on immunological and antioxidant responses, weight gain and minimization of coccidiosis of newborn lambs. (December 2018) - Cazarotto, Chrystian J.; Boito, Jhonatan P.; Gebert, Roger R.; Reis, João H.; Machado, Gustavo; Bottari, Nathieli B.; Morsch, Vera M.; Schetinger, Maria R.C.; Doleski, Pedro H.; Leal, Marta L.R.; Baldissera, Matheus D.; Da Silva, Aleksandro S.
Abstract: The aim of this study was to evaluate the metaphylactic effect of minerals on immunological and antioxidant responses, as well as performance and prevention of coccidiosis in newborn lambs. We divided 110 newborn lambs into two groups (55/group): control (untreated) and treated with two doses of 0.33 mL/kg of a mineral complex (zinc, copper, selenium, and manganese) on day of life (DOL) 1 and 30. Total blood was collected at DOL 1, 15, 30 and 45 to measure antioxidant enzymes, biochemical and immunology analyses, and haemogram. Treated animals were heavier ( P  < .05) than untreated lambs on DOL 15 and 45, but not on DOL 30 due to a coccidiosis outbreak. Catalase activity did not differ between groups, while superoxide dismutase and xanthine oxidase activities were higher ( P  < .05) in treated lambs compared with control animals. Serum levels of total protein and globulins were higher (P < .05) in treated animals (DOL 15, 30 and 45). A significant increased on the number of lymphocytes (DOL 45), as well as on seric levels of immunoglobulins (IgM and IgG) was observed in treated animals (DOL 15 and 30). Serum Ig levels remained constant throughout the experiment in the treated group, but fluctuated in the control group. Serum glucose levels were greater in treated animals (DOL 15 and 30). It is possible to conclude that subcutaneous administration of minerals has beneficial effects on lambs by increasing antioxidant and immunological defenses, reflected by greater weight gain, which could mitigate the impact of coccidiosis. Highlights: Mineral complex based on zinc, manganese, copper and selenium in newborn lambs was used. The mineral complex indirectly mediates activation of antioxidant systems, and may stimulate immune responses. Metaphylactic effect of minerals contributed to increase weight gain. Subcutaneous administration of minerals improved health, and consequently minimized coccidiosis.